Online forums: promotion of parental competences in Positive Parent program - Suárez Perdomo, Arminda; Rodríguez, Juan A.; Rodrigo, María José (Revista Complutense de Educación, 2024)
The diversity of discourse during the online program "Educar en Positivo" is analyzed using the ATLAS.ti v9 tool. The participants were 54 Spanish-speaking mothers and fathers, analyzing their messages in forums after carrying out activities of three modules. According to the grounded theory, eight dimensions were extracted: reflection process, parental concern, role axiology, parental stress, external model, parental agency, own model and need for training. Of these, 17 categories were observed in 301 citations. They highlight the reflection on their own practices and ideas, in relation to what they should be and other people's models, as well as the concern and stress linked to parenthood. In a differential way in Module 1, the concern about the dangers on the Internet and the need for training stand out; in Module 2 on relationships in adolescence and Module 3 on education in childhood highlights self-efficacy, ought to be, motivation for change, family reconciliation and exhaustion in the parental task. In short, this online program offers a space for building skills in which the participants analyze their actions in the face of the different challenges depending on the areas of socialization and the ages of their sons and daughters.
Keywords: Qualitative content analysis; ATLAS.ti; online parental support; positive parenting